2022
DOI: 10.1186/s12929-022-00810-5
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the physiological roles of mazEF toxin–antitoxin system on clinical MRSA strain by CRISPR RNA-guided cytidine deaminase

Abstract: Background Curiosity on toxin–antitoxin modules has increased intensely over recent years as it is ubiquitously present in many bacterial genomes, including pathogens like Methicillin-resistant Staphylococcus aureus (MRSA). Several cellular functions of TA systems have been proposed however, their exact role in cellular physiology remains unresolved. Methods This study aims to find out the impact of the mazEF toxin–antitoxin module on biofilm forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The presence of a large number of vapBC toxin-antitoxin (TA) systems within the group of thermoacidocphilic archaea, including S. acidocaldarius , implies a possible role in adapting to their specific environments. Because bacterial TA systems are involved in programmed cell death or persister cell formation during stress conditions [2], we speculated that depending on the stress conditions, S. acidocaldarius might activate or deactivate specific vapBC systems to determine the fate of the cells. In our earlier research, we have demonstrated how the vapBC system plays a part in adapting to various stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a large number of vapBC toxin-antitoxin (TA) systems within the group of thermoacidocphilic archaea, including S. acidocaldarius , implies a possible role in adapting to their specific environments. Because bacterial TA systems are involved in programmed cell death or persister cell formation during stress conditions [2], we speculated that depending on the stress conditions, S. acidocaldarius might activate or deactivate specific vapBC systems to determine the fate of the cells. In our earlier research, we have demonstrated how the vapBC system plays a part in adapting to various stresses.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the investigation of toxin-antitoxin (TA) systems has gained attention due to their essential roles in regulating bacterial growth, aiding survival under stressful conditions, and their potential implications in bacterial virulence and antibiotic resistance [1, 2]. TA systems consist of a pair of closely linked genes encoding a stable toxin and a labile antitoxin, wherein the antitoxin neutralizes the toxin’s effects, maintaining cellular equilibrium [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the era of synthetic biology, with the fast expansion of the toolbox for modifying the genomes of living organisms, base-editing tools have attracted interest because of specific features: independence of endogenous cellular DNA repair pathways, lower cytotoxic effects than with other Cas9-based tools, high efficacy, which means that there is no need for selection markers, possibility of multitargeting, and the lack of a scar at the edited locus. These properties make BE promising tools for clinical usage in human therapeutics ( 60 ) and for multiple applications in plants ( 51 , 61 ) and microorganisms of medical or biotechnological relevance ( 62 64 ). Because of their high efficacy, BE are particularly attractive for bacteria that are difficult to transform, as, ultimately, one single transformant can be enough to obtain a mutant.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstrated deceleration in protein synthesis under VapC expression and bacterial growth slowdown resultant from tRNA slicing reveals the toxin role as the accurate tuner of the translation process and contributes to stress response development, in particular, under treatment with antibiotics inhibiting ribosome activity [15]. In turn, the mazEF module is associated with the formation of persisting and dormant bacteria [16,17] and affects antibiotic resistance [18] as well as susceptibility to different environmental stresses [9,19].…”
Section: Introductionmentioning
confidence: 99%